2022
DOI: 10.3390/v14061184
|View full text |Cite
|
Sign up to set email alerts
|

Infection Route Impacts the Pathogenesis of Severe Fever with Thrombocytopenia Syndrome Virus in Ferrets

Abstract: The threat of severe fever with thrombocytopenia syndrome (SFTS) to public health has been increasing due to the rapid spread of the ticks that carry the causative viral agent. The SFTS virus (SFTSV) was first identified in China and subsequently detected in neighboring countries, including South Korea, Japan, and Vietnam. In addition to the tick-mediated infection, human-to-human transmission has been recently reported with a high mortality rate; however, differential study of the pathogen has been limited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In contrast to the sparsity of information available on HRTV pathogenesis, much more is known about the pathogenesis of SFTSV in a range of wild-type and immunodeficient model systems. Though many of the species investigated were of limited value for better understanding SFTSV infections in humans, lacking some key features of the disease process (summarized in a recent review by Sun et al [34]), studies in ferrets [38], cats [39], and non-human primates [40][41][42] have found that these species may share some key features of disease in humans. Studies in rhesus macaques, for example, revealed that they have patterns of viremia, tissue distribution, and pathology which mirror those observed in human SFTSV infections [40,42].…”
Section: Viral Pathogenesismentioning
confidence: 99%
“…In contrast to the sparsity of information available on HRTV pathogenesis, much more is known about the pathogenesis of SFTSV in a range of wild-type and immunodeficient model systems. Though many of the species investigated were of limited value for better understanding SFTSV infections in humans, lacking some key features of the disease process (summarized in a recent review by Sun et al [34]), studies in ferrets [38], cats [39], and non-human primates [40][41][42] have found that these species may share some key features of disease in humans. Studies in rhesus macaques, for example, revealed that they have patterns of viremia, tissue distribution, and pathology which mirror those observed in human SFTSV infections [40,42].…”
Section: Viral Pathogenesismentioning
confidence: 99%